2016
DOI: 10.2298/sarh1610470t
|View full text |Cite
|
Sign up to set email alerts
|

Anterior and middle superior alveolar block is efficient for maxillary premolar teeth extractions regardless of the injection system or anesthetic with adrenaline used

Abstract: The anterior and middle superior alveolar nerve block may be recommended if maxillary permanent premolars have to be extracted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The present study aimed to understand the anatomical basis of AMSA anesthetic injection. Although this technique has been reported to be effective in many clinical studies [10][11][12][13], others have questioned its predictability [14,15]. Some authors have questioned the Many studies have compared the thickness and the density of buccal and palatal cortices using CBCT-based analysis, although for a different purpose [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…The present study aimed to understand the anatomical basis of AMSA anesthetic injection. Although this technique has been reported to be effective in many clinical studies [10][11][12][13], others have questioned its predictability [14,15]. Some authors have questioned the Many studies have compared the thickness and the density of buccal and palatal cortices using CBCT-based analysis, although for a different purpose [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Tomić et al compared the anesthetic efficacy of AMSA injections by using three different anesthetic solutions: 3% mepivacaine plain, 2% lignocaine with adrenaline (1:80000), and 4% articaine with adrenaline (1:100000). They concluded that predictable efficacy of AMSA injections was achieved for the extraction of the permanent premolars, regardless of the LA used [32]. Both of these studies also reported an insignificant difference in pain on injection with different LA solutions and vasoconstrictors [3032].…”
Section: Factors Affecting the Success Of Amsa Injectionsmentioning
confidence: 99%
“…They concluded that predictable efficacy of AMSA injections was achieved for the extraction of the permanent premolars, regardless of the LA used [32]. Both of these studies also reported an insignificant difference in pain on injection with different LA solutions and vasoconstrictors [3032]. The conflicting results in these two studies regarding the efficacy of different LA solutions for AMSA injections may be attributed to the intended procedure.…”
Section: Factors Affecting the Success Of Amsa Injectionsmentioning
confidence: 99%
See 1 more Smart Citation